Penelope, Ulysses and the “Odyssey” in Spanish contemporary poetry written by women - Marina Sáez, Rosa María (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This article studies some Spanish contemporary poems written by women about the Odysseic myth. It takes an special interest in different functions that this myth acquires in each author as an evidence of its capacity of adaptation to new literary and communicative contexts.